Celestial bodies : a novel - HÌ£aÌrithiÌ, JuÌkhah (Catapult, 2019)
"In the village of al-Awafi in Oman, we encounter three sisters: Mayya, who marries after a heartbreak; Asma, who marries from a sense of duty; and Khawla, who chooses to refuse all offers and await a reunion with the man she loves, who has emigrated to Canada. These three women and their families, their losses and loves, unspool ... against a backdrop of a rapidly changing Oman, a country evolving from a traditional, slave-owning society into its complex present"--